Should We Say Goodbye to Latent Constructs to Overcome Replication Crisis or Should We Take Into Account Epistemological Considerations? - Hanfstingl, Barbara (Frontiers in Psychology, 2019)
The paper discusses theoretical and epistemological problems concerning validity of psychological science in the context of latent constructs. I consider the use of latent constructs as one reason for the replicability crisis. At the moment, there exist different constructs describing the same psychological phenomena side by side, and different psychological phenomena that are reflected by the same latent construct. Hagger called them déjà-variables, which lead to a decreasing validity of measurements and inhibit a deeper understanding of psychological phenomena. To overcome this problem, I suggest a shift of theoretical and epistemological perspective on latent constructs. One main point is the explicit consideration of latent constructs as mental representations, which changes objects and are changed by objects via assimilative and accommodative processes. The explicit orientation towards assimilation and accommodation allows the control of normally automatized processes that influence our understanding of psychological phenomena and their corresponding latent constructs. I argue that assimilation and accommodation are part of our research practice anyway and cause the mentioned problems. For example, taking a measurement is an assimilative process, and thus a high measurement error should lead to an increase of accommodative processes. Taking into account these considerations, I suggest consequences for research practices, for individual researchers and for the philosophy of science.